HUBUNGAN LINGKUNGAN SEKOLAH DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR IPS SISWA KELAS VIII DI MTsN AMUNTAI - Uswatun Hasanah (Universitas Lambung Mangkurat, 2015)
This research aims to (1) determine the correlation between school environment and learning achievement in IPS of the VIII grade students of MTsN Amuntai, (2) determine the correlation between learning motivation and learning achievement in IPS of the VIII grade students of MTsN Amuntai, (3) determine the correlation among school environment, learning motivation, and learning achievementin IPS of the VIII grade students of MTsN Amuntai. The method used in this research was quantitative method. This research was conducted to the VIII grade students of MTsN Amuntai. The research samples were determined by using Purposive Sampling, the sample used in this study were 138 students with population 292 students. The data were analyzed using the correlation technique of Pearson Product Moment, t-test and multiple correlation. The instruments were tested in advance with the aim of analyzing the validity and reliability. The hypothesis testing used Pearson Correlation Product Moment, t test and multiple correlation with SPSS 14.0 for window at the significant level of 0.05 (5%). The result of the research shows that school area has strong correlation with the learning achievement in IPS. The strong correlation can seen from the ry1 value which is 0.420, in the interval 0.400-1.000 with very strong criteria. Learning motivation has strong correlation with the learning achievement in IPS. The strong correlation can be seen from the ry2 value 0.199, which is in the interval of 0.000-0.199 with strong criteria. Those three factors are related to each other in supporting the learning achievement in IPS. Pursuant to result of research, hence suggested (1) Teacher expected can make student is not saturated bored and to follow lesson of IPS; (2) Student expected can exploit environment which is kondusif; (3) Ministry of religion to be more pay attention existing facilities and basic facilities each every school.Key words: school environment, learning motivation, and learning achievement of social studies